Nurul Ilmi, Sultan, Adi, Fitri: ANALISIS PENGARUH HARGA, KUALITAS JASA, DAN PROMOSI TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN JASA LAUNDRYFREYA DI KECAMATAN BAJO KABUPATEN LUWU - Nurul Ilmi; Sultan; Fitri; Adi (BJRM (Bongaya Journal of Research in Management), 2025)
This study aims to assess the impact of pricing on customer satisfaction at Freya Laundry in Bajo District, Luwu Regency. To ascertain the impact of service quality on customer satisfaction at Freya Laundry, Bajo District, Luwu Regency. To ascertain the impact of promotion on customer satisfaction at Freya Laundry, Bajo District, Luwu Regency. To ascertain the concurrent impact of pricing, service quality, and promotion on customer satisfaction at Laundr Freya, Bajo District, Luwu Regency. This research employs a quantitative methodology. The study population comprises clients of Launder Freya, located in Bajo District, Luwu Regency. This survey comprised 94 respondents. The sampling technique use the Slovin formula. The employed instrument tests included validity tests, reliability tests, multiple linear regression tests, and classical assumption tests, specifically normality tests, multicollinearity tests, and heteroscedasticity tests. Hypothesis tests utilised comprised t tests (partial hypothesis tests), f tests (simultaneous hypothesis tests), and determination tests, all conducted using SPSS version 31. The findings of this study indicate that pricing directly affects customer satisfaction, evidenced by a t-value of 3.005 and a significance value of 0.003. The quality of service significantly influenced customer satisfaction, evidenced by a t count of 3.549 and a significance value of less than 0.001. Promotion does not influence customer satisfaction, evidenced by a t-value of -0.410 and a significance level of 0.683. These three independent factors concurrently influence customer satisfaction, yielding a F value of 40.547 with a significance level of less than 0.001. Keywords: Price, Service Quality, Promotion, and customer satisfaction